THE EFFECT OF WORK STRESS ON EMPLOYEE TURNOVER INTENTION IN PT BANK RAKYAT INDONESIA MAKASSAR BRANCH AHMAD YANI - Nurfitriani Nurfitriani; Arwin Arwin (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
This study aims to analyze and explain the effect of work stress on the employee turnover intention in PT Bank Rakyat Indonesia Makassar Branch Ahmad Yani. The hypothesis proposed in this study is that job stress has a positive effect on the employee turnover intention in PT Bank Rakyat Indonesia Makassar Branch Ahmad Yani. The population in this study were 243 employee of PT Bank Rakyat Indonesia Makassar Branch Ahmad Yani. However in this study, not whole the populations were being the research object, but only a part of the population. This study is expecting that the results obtained would describe the characteristic of the population itself. The sample in this study was determined based on the Slovin formula (Umar, 2008: 68), namely 71 employee. The data used are primary data and secondary data, data collection techniques are interviews, questionnaires, and observations. Data analysis used Regression Analysis, Partial Test (t test) and Classical Assumption Test consisting of the Normality Test, Heteroscedasticity Test and Multicolonierity Test. The results show that the hypothesis is rejected where the job stress variable has no effect on the turnover intention. H1 is rejected and H0 is accepted, meaning that the higher the level of employee work stress, would make lower turnover intention, on the contrary the lower level of employee work stress, makes higher turnover intention.